Recent progress on the discovery of antiamoebic agents. Issue 21 (1st November 2016) - Hayat, Faisal; Azam, Amir; Shin, Dongyun
Graphical abstract: Abstract: A large number of protozoans infect humans but Entamoeba histolytica is the only organism responsible for causing amoebiasis, a deadly disease after malaria. Numerous heterocycle-based antiamoebic agents have been previously synthesized as E. histolytica inhibitors and while some of these agents have shown moderate activity, the search for a novel and ideal antiamoebic compound is still ongoing. In this digest Letter, we present the latest data on antiamoebic agents from 2011 to 2016 based on the different classes of heterocyclic agents.